Analysis of bulk solids attrition in pneumatic conveying by distinguishing between process and material parameters - Peukert, Wolfgang; Frye, Lars (BHR Group Limited, 2004)
For the investigation of attrition, it is distinguished between process and material parameters. Therefore, attrition is regarded as a result of a process function determining the stress conditions the particles are subjected to and a material function summarizing the material specific response to these. The process function was determined by employing computational fluid dynamics (CFD) and by analyzing experimental results as well as discrete element simulations (DEM) carried out at Glasgow Caledonian University. The material function was determined by carrying out attrition experiments on varying scales and by measuring thermo-mechanical material properties with dynamic mechanical analysis (DMA).
Keywords: attrition; material; parameter; process; simulation